Trademarks, comparative advertising, and product imitations: An untold story of law and economics - Tim W. Dornis; Thomas Wein (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2016)
Comparative advertising is a daily phenomenon in the modern landscape of commercial communication. Interestingly, however, a deep dichotomy exists between the American legal doctrine on comparative advertising and its European counterpart. Whereas American lawyers have cultivated a rather liberal stance, Europe has preserved its historical penchant for prohibiting comparative advertising. This divergence is puzzling when it concerns the handling of so-called imitation claims and product comparison lists, especially with respect to luxury perfumes and smell-alikes, or other exclusive products and their cheaper imitations. European lawmakers, pressured by the French perfume industry, have integrated a per se prohibition on imitation claims into the European Directive on Misleading and Comparative Advertising. On the other hand, in the US, there is virtually no restriction on imitation claims and comparison lists beyond the prevention of consumer confusion and deception. Indeed, the Lanham Act expressly excludes trademark dilution claims in cases of comparative advertising. To date, however, there has been no comprehensive economic analysis of this panorama. This article seeks to fill that gap. In conducting such an analysis, it reveals severe defects in both the American and European rules on comparative advertising. It also provides the basis for a more specific reconceptualization of the field and helps formulate a theoretical and practical framework for lawmaking and policymaking.
Keywords: 330